The Development Of System For Algorithms Visualization Using Simjava - Jamil Alsayaydeh, Jamil Abedalrahim; Ahmad Idil, Abdul Rahman; Zainon, Maslan; Aziz, Azwan; Zikri Abadi, Baharudin; Oliinyk, Andrii (Asian Research Publishing Network, 2020)
Algorithm visualization which is a form of high-level dynamic visualization of software that uses user interface techniques to portray and monitor the computational steps of algorithms. Moreover, algorithm visualization systems are also useful tools in algorithm engineering, particularly at several stages during the design, implementation, analysis, tuning, experimental evaluation, and presentation of the algorithms process. Algorithms are a captivating use case for visualization. It does not simply fit data to a chart to visualize an algorithm, there is no main data set. Rather there are consistent principles that depict conduct. This is because algorithm visualizations are so uncommon, as designer's experiment with novel forms to better communicate. Algorithm visualization (AV) uses graphics to portray an algorithm's actions. AV holds the promise of helping computer science students understand algorithms more effectively and in more prominent profundity. The purpose of this study is to design a system for sorting algorithm visualization and implement the system.